Terrorism in Indonesia after Islamic State - Temby, Quinton (ISEAS - Yusof Ishak Institute, 2020)
The emergence of the Islamic State (IS) movement in Indonesia in 2014 re-energized violent extremism in Indonesia. As a result of effective counterterrorism policing, however, IS networks have been decimated and the structure of jihadism in Indonesia has shifted from organizations to autonomous networks and cells, increasingly organized via the Internet.Although support for violent extremism in Indonesia remains marginal, cells of IS followers maintain a low-level capacity to conduct lethal attacks against civilian and government targets.